Kajian Studi Literatur: Empat Mitos Umum Matematika Menurut Reuben Hersh - Habibie, Zulqoidi R.; Rochmad, Rochmad; Isnarto, Isnarto (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2022)
This study aims to re-describe the Four General Myths of Mathematics according to Reuben Hersh. The method to be used for this study is the study of literature. While the literature sources used are first, the main source consists of the philosophy of science book by Reuben Hers. Second, supporting sources are obtained from journal articles related to the discussion. Furthermore, the data obtained will be compiled, analyzed, and concluded so as to get conclusions. The results of the study show that mathematics has four common errors, namely 1) Unity; 2) Universality; 3) Certainty; 4) Objectivity.